Clinical efficacy of open palmar approach combined with distal radial cancellous bone transplantation and internal fixation in the treatment of scaphoid nonunion - Li, Gang; Li, Rui; Long, Jafeng; Ou, Xuehai; Shi, Shaoyan (Frontiers in Surgery, 2024)
BackgroundTo investigate the clinical efficacy of the open palmar approach combined with distal radial cancellous bone transplantation and internal fixation in the treatment of scaphoid nonunion.MethodsFrom March 2019 to March 2022, our center conducted a clinical observation on 19 patients with scaphoid nonunion, including 14 males and 5 females, aged 18–63 years, with an average age of (43.5 ± 15.5) years. The surgical approach involved open palmar access combined with distal radial cancellous bone transplantation and internal fixation, followed by three months of immobilization with a splint. Postoperative x-ray examinations were performed at 6 months to observe bone graft healing and functional recovery.ResultsFollow-up of the 19 patients ranged from 6 to 24 months, with an average of 18 months. All patients achieved bony union, with an average healing time of 6 months. Postoperatively, wrist joint function was assessed using the modified Mayo wrist joint function scoring criteria: excellent in 15 cases, good in 2 cases; an excellent and good rate of 89.5%.ConclusionThe open palmar approach combined with distal radial cancellous bone transplantation and internal fixation is effective in treating scaphoid nonunion. The procedure is minimally invasive, allowing complete exposure of the fractured end of the scaphoid and the distal radius through the same incision. It facilitates easy cleaning of the fracture end, as well as convenient bone harvesting, grafting, and internal fixation. The postoperative efficacy is reliable, demonstrating significant advantages in the treatment of scaphoid nonunion.